PERBEDAAN ASUPAN ENERGI DAN PROTEIN PADA SIANG HARI ANTARA ANAK TAMAN KANAN-KANAK DI SEKOLAH DENGAN MODEL SCHOOL FEEDING DAN NON SCHOOL FEEDING - Sukendro, Niken Putri; Sunarti, . (Universitas Ahmad Dahlan, 2012)
Background: Kindergarten (TK) is the beginning in introducing a child with a social environment outside the family. Kindergarten-age children is going through a relatively rapid growth and is a group vulnerable to nutritional problems especially energy and protein deficiency. Nutrition got by children in everyday food consumption has a big role for the children. Food facility (School feeding) is expected to be able to meet the nutritional needs of children that consist of morning snack, lunch and afternoon snack. The aim of this study is to determine the differences of energy and protein intakes during the day of kindergarten students at school with school feeding and non-school feeding model in Blimbing, Sukoharjo, Central Java. Method: This was a quasi experimental research design. Numbers of the study subjects consist of 38 5-7 years old kindergarten students from schools with school feeding and non-school feeding. Research tools used is 24-hour recall form. Data analysis used independent t-test to determine differences in the energy and protein intakes. Results: The consumption average of energy during the day (7.30 am-03.30 pm) of the kindergarten children with school feeding and non-school feeding a model is 572,5 and 640,5 kcal. While the average consumption of protein during the day (7.30 am-03.30 pm) in kindergarten children with school feeding and non-school feeding a model was 20,3 and 19,3 gr. Conclusion: There was no difference of the energy and protein intakes during the day (p> 0.05) between the two types of the kindergarten children in school. Keywords: kindergarten, energy intake, protein intake, school feeding, non-school feeding